Evaluation of professional stress in IT professionals - Karthikeyan Arasu, S.; Dhivakar, R.; Cibi Chakravarthi, J.; Kausik, M.; Arun Kumar, M. (International Journal Of Community Medicine And Public Health, 2019)
Background: Stress has become common among the working people in this era. This may lead to further dire psychological consequences such as anxiety, depression etc. India being the information technology (IT) hub with lakhs involved as IT Professionals, there is a need to assess prevalence of professional stress. Not many studies have been conducted regarding this research topic in urban areas. Hence, this study has been exclusively done in Coimbatore which is an urban area in which IT is still developing. Aim of the study was to assess the stress levels of IT professionals in a software company in urban Coimbatore, Tamil Nadu. Methods: Cross–Sectional Study based on a validated questionnaire based on professional life stress scale (PLSS). Results: Out of the 105 employees interviewed 68% were in mild degree of stress. The remaining 32% had moderate degree of stress and none of the participants had high degree of stress. Conclusions: India being a leading sector in IT, its development largely depends on its employees’ physical and mental health. Occupational stress (job stress/work stress) need to be kept harnessed and minimized to provide conducive work environment in the organization.